Microencapsulation of alpha-mangostin into PLGA microspheres and optimization using response surface methodology intended for pulmonary delivery. (30th April 2013) - Elsaid Ali, Aimen Abdo; Taher, Muhammad; Mohamed, Farahidah
Abstract: Documented to exhibit cytotoxicity and poor oral bioavailability, alpha-mangostin was encapsulated into PLGA microspheres with optimization of formulation using response surface methodology. Mixed levels of four factors Face central composite design was employed to evaluate critical formulation variables. With 30 runs, optimized formula was 1% w/v polyvinyl alcohol, 1:10 ratio of oil to aqueous and sonicated at 2 and 5 min time for primary and secondary emulsion, respectively. Optimized responses for encapsulation efficiency, particle size and polydispersity index were found to be 39.12 ± 0.01%, 2.06 ± 0.017 µm and 0.95 ± 0.009, respectively, which matched values predicted by mathematical models. About 44.4% of the encapsulated alpha-mangostin was released over 4 weeks. Thermal analysis of the microspheres showed physical conversion of alpha-mangostin from crystallinity to amorphous with encapsulated one had lower in vitro cytotoxicity than free alpha-mangostin. Aerodynamic diameter (784.3 ± 7.5 nm) of this alpha-mangostin microsphere suggests suitability for peripheral pulmonary delivery.